Indoor Map Construction Methods for Indoor Location Services - Bai, Mingchen (International Journal of Computer Science and Information Technology, 2025)
This study proposes a hybrid map model integrating building entity elements with network topology structures, addressing the challenges of constructing building map models in complex and dynamic geographical environments. Using Building Information Modeling (BIM) as the core data source and leveraging Geographic Information System (GIS) integration principles, the model synthesizes both geometric/attribute data of buildings and dynamic geospatial environmental variables. Building upon this hybrid model, we further design and implement an engine-based scheduling and loading framework optimized for building maps. The solution enables efficient cross-platform loading (web and mobile clients), ensuring seamless user access and interaction with building maps across diverse devices. This approach significantly enhances the accessibility and practical utility of map applications.